Analisis Konstitusional terhadap Perlindungan Hak Asasi Manusia dalam Sistem Hukum Indonesia - Seri Mughni Sulubara; T. Saiful Basri; Iskandar Iskandar (Institut Teknologi dan Bisnis Semarang, 2024)
Human rights are basic rights that are inherently inherent in humans, are universal and lasting. Human rights must be protected, respected, defended, and must not be ignored, reduced, or deprived by anyone, including by the government and state apparatus. The state, through the 1945 Constitution and a number of legal instruments, has guaranteed the protection of human rights. Human rights are the basic rights of every person. The guarantee of human rights freedom has been regulated through several articles in the 1945 Constitution. Every person is entitled to recognition, guarantees, protection, and fair legal certainty in human rights, as well as equal treatment before the law (equality before the law) (Sulubara, 2024). In this research, a descriptive-analytical method with a normative juridical approach is used. Through the use of legal materials and a comprehensive literature review, it was found that while there is a strong legal framework supporting the protection of human rights, there are still significant challenges in its implementation. These challenges include weak legal culture, inequality, discrimination, corruption, and weak law enforcement. Constitutional Basis for Human Rights Protection in Indonesia The 1945 Constitution, which is the highest legal basis in Indonesia, has regulated various human rights in several articles. Since the first amendment in 1999, the 1945 Constitution has further emphasized and strengthened the position of human rights. Some of the articles that explicitly regulate the protection of human rights are (Saf & Natsif, 2019). Article 28A to Article 28J of the 1945 Constitution, which regulates the right to life, personal freedom, protection from torture, the right to work, freedom of association, and the right to justice. Article 28I, which regulates rights that cannot be reduced under any circumstances (non-derogable rights) such as the right to life, the right not to be tortured, and the right to be free from slavery. Article 28D provides for the right of every person to be recognized as an equal person before the law and to receive equal treatment before the law. According to Article 28I of the 1945 Constitution, the state is obliged to respect, protect and fulfill human rights. The state is also required to create a legal system that supports the fulfillment of these rights.